PENGALAMAN PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) DALAM MEMFASILITASI MASYARAKAT BELAJAR SEPANJANG HAYAT - Mita Septiani (Jurnal Ilmiah Visi, 2015)
The objective of this research is to provide a thorough description of the Community Learning Centres (CLC) experiences in facilitating the local communities to implement lifelong learning. This study is a qualitative research with a phenomenology method conducted at North Jakarta in 2015. The data were collected at six CLCs through informan observation using depth interview, observation, document study, and recording as from March through June 2015. The data analysis and interpretation indicated that (1) the implementation of CLC roles and function were categorized in eight themes: (a) indentifying the community needs, (b) promoting the education program, (c) providing potential resources, (d) building cooperation with partners, (e) monitoring and evaluating program,(f) conducting alternative education, (g) providing information and learning centres, (h) conducting community development; (2) analyzing the strengths and weakness of CLCs; and (3) giving recommendation to improve the roles of CLCs in facilitating lifelong learning society at North Jakarta.The findings lead to the recommendation for policy makers, CLC management, learning community, educational technology, and further researchers about how to facilitate learning in non-formal education, especially in CLCs.